1975
DOI: 10.1016/0018-506x(75)90005-7
|View full text |Cite
|
Sign up to set email alerts
|

Anti-estrogenic suppression of the lordosis response in female rats

Abstract: The anti-estrogen, Cl 628, was used to suppress the lordosis response induced by sequential injections of estrogen and progesterone in ovariectomired (OVX) female rats. Appropriate doses of Cl 628 completely abolished sexual receptivity in females administered estradiol benzoate (EB) in sesame oil. This behavioral effect could be attenuated by providing increased quantities of EB or decreased quantities of CI 628. Antiestrogenic effects on lordosis induced by free estradiol in saline (E) were assessed after fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1976
1976
1987
1987

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 37 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Another explanation of the difference is that a depot injection of OB in oil was given intramuscularly in the present study, whereas Findlay et al (1973) infused oestradiol-17ß in saline into the jugular vein. The more prolonged exposure to oestrogen in the present work may have diminished the effects of hypothalamic insensitivity, as suggested by Powers (1975). It is likely that the duration of exposure to oestrogen at natural oestrus would also be sufficient to diminish the effects of reduced sensitivity to oestrogen for LH release by the hypothalamus.…”
Section: Discussionmentioning
confidence: 55%
“…Another explanation of the difference is that a depot injection of OB in oil was given intramuscularly in the present study, whereas Findlay et al (1973) infused oestradiol-17ß in saline into the jugular vein. The more prolonged exposure to oestrogen in the present work may have diminished the effects of hypothalamic insensitivity, as suggested by Powers (1975). It is likely that the duration of exposure to oestrogen at natural oestrus would also be sufficient to diminish the effects of reduced sensitivity to oestrogen for LH release by the hypothalamus.…”
Section: Discussionmentioning
confidence: 55%
“…This means that the magnitude of the inhibition of a given antiestrogen dose depends on the amount of estradiol administered, such that high doses of estradiol can prevent the behavioral inhibition of the antiestrogen [13]. In experi ment I, we found that 1% TAM, intracranially, antagonized a systemic treatment of 5% estradiol compared with control females, yet we saw no behavioral inhibition the following week when intracranial treatment conditions were reversed.…”
Section: Discussionmentioning
confidence: 67%
“…Some insight into the nature of these mechanisms has been gained by testing the effects on lordosis of various pharmacological agents which can disrupt potentially relevant neurochemical processes. These studies have suggested that estradiol interactions with brain cell nuclei, resulting in altered protein synthetic activities, are necessary for the eventual expression of lordosis [35,37,41,45]. Because approximately 18-24 hr must elapse after estradiol administration before progesterone can facilitate sexual receptivity [13,18,38], it is reasonable to suppose that this latent period represents the time during which relevant metabolic processes occur.…”
Section: Lordosismentioning
confidence: 99%